Attitudes of the Chilean Right toward Jews : from acceptable undesirables to respected businessmen - Guzmán, Gustavo 1981- (Jewish Latin America, 2022)
"This is the first book in English to discuss the changing attitudes of the Chilean right toward Jewish immigrants and the State of Israel from the 1930s onwards. Jewish Chileans have ascended rapidly from the status of undesirable immigrants to middle and upper-middle class, facing less obstacles than their Argentine coreligionists. Particular emphasis is given to the failed struggle to extradite war criminal Walter Rauff and to the years of the military dictatorship headed by general Augusto Pinochet. By the 1970s, Israel seemed a strong pro-Western barrier to the expansion of communism and Islamic fundamentalism"